Impact of Stress on the Academic Performance Among 4th Year College Engineering Students at Bestlink College of the Philippines: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Some struggle with choosing their path. They will find work or go to college. Others go tocollege either by choice or by force, and some would rather begin their careers as employeesor business owners. However, there is a third option, where one can do both: become aworking student, when hard work must be present to get the desired diploma and to pursuetheir life dreams. Previous studies do not explain or describe how coping mechanisms assistworking college students in performing well academically. As a result, the purpose of thisstudy was to address a research gap by obtaining additional information about how college-working students, specifically engineering-working students, manage stress and what theircoping techniques are.The results obtained from the data gathering were done through a series of interview sessionswith 4th-year college engineering working students, who were the chosen respondents of thestudy. The study found that students use extracurricular activities as a stress-relievingstrategy. This research also concludes that the stressors that students experience have ahuge impact on their academics. However, by using time management methods, students areable to balance their academic and work duties.The majority of study participants provided insight into the complex and varied waysindividuals deal with difficult circumstances. Different coping mechanisms were used by thestudy's participants. The data gathered in this study highlights numerous important stressesthat have an effect on individuals across a range of circumstances. One of the issues thatcame up most frequently was time management.
Keywords: Psychology